Still Ours to Lead America, Rising Powers, and the Tension between Rivalry and Restraint - Jones, Bruce D. 1969- (Brookings Institution Press, 2014)
Is the United States still a "superpower"? How are the rising powers establishing themselves in international politics and security? What is the future of global stability?For over a decade, Bruce Jones has had a front-row seat as the emerging powers-principally China, India, and Brazil, but also Turkey, Indonesia, Korea, and others-thrust themselves onto the global stage. From Delhi to Doha to Beijing to Brasilia, he's met with the politicians, diplomats, business leaders, and scholars of those powers as they craft their strategies for rising influence-and with senior American officials as they forge their response. In Still Ours to Lead, Jones tells a nuanced story of American leadership. He artfully examines the tension between the impulse to rival the United States and the incentives for restraint and cooperation among the rising powers. That balance of rivalry and restraint provides the United States with a continued ability to solve problems and to manage crises at roughly the same rate as when American dominance was unquestioned. Maintaining the balance is central to the question of whether we will live in a stable or unstable system in the period to come. But it just so happens that this challenge plays to America's unique strength-its unparalleled ability to pull together broad and disparate coalitions for action. To succeed, America must adapt its leadership to new realities
Description based on publisher supplied metadata and other sources
Keywords: Außenpolitik; Globalisierung; Politik; Globalization -- Political aspects; United States -- Foreign relations -- 21st century; World politics -- 21st century; Internationales politisches System; Auflösung; Weltordnung; Hegemonie; Internationale Politik; Zukunft; Weltpolitik; USA